Aluminium Tertiary Industry Waste and Ashes Samples for Development of Zeolitic Material Synthesis - Denise Alves Fungaro; Kátia Cruz Silva; Alaa El Din Mahmoud (Journal of Applied Materials and Technology, 2021)
Wastes generated in large amounts have been recognized as sustainable sources of raw materials for the synthesis of adsorbents. The synthesis of zeolite through wastes recycling of two different ash sources (coal bottom ash and sugarcane waste ash) and industrial aluminum waste was evaluated. The molar ratio of SiO2/Al2O3 for zeolite 4A formation was achieved by the addition of aluminum waste from tertiary industry as aluminum source. Coal bottom ash and sugarcane waste ash were used as a source of both silica and alumina. The synthesized materials were characterized using X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and cation exchange capacity (CEC). The analysis of the properties of the products demonstrates that the by-products can be used to produce zeolite A. The utilization of synthesized zeolites as adsorbent for cadmium removal from aqueous solution was conducted following the concept of implementation of utilization of waste materials as a component of the circular economy in the wastewater sector.